Detection of platelet vesicles by flow cytometry. (3rd April 2017) - Nolan, John P; Jones, Jennifer C
Abstract: The composition and function of platelet-derived extracellular vesicles (EVs) in health and in disease are a major topic of investigation in biomedical research. However, efforts to delineate specific molecular repertoires and roles for different types of EVs in the circulation are limited not only by the lack of flow cytometers capable of analyzing submicron- and nano-materials across the full size spectrum of plasma EVs, but also by the lack of standardized methods and reference materials that would permit inter-laboratory reproducibility for these analyses. In this review, we summarize the flow cytometry of EVs, with a focus on platelet vesicles in plasma. In addition to delineating the basic principles that govern what precautions must be considered when using flow cytometry for the analysis of platelet vesicles, we provide an overview for how to standardize, control, annotate, and report EV flow cytometry data reproducibly, while looking forward to a next generation of high sensitivity instruments for the analysis of EVs and other submicron biomaterials in the circulation.